A petroleum pipeline repair coating composition and its preparation method and application
By using compositions such as composite epoxy resin and modified epoxy resin, the problem of insufficient waterproofness and aging resistance of petroleum pipeline repair coatings is solved, and excellent performance in complex environments is achieved to meet the needs of petroleum pipeline repair.
Patent Information
- Application Number
- CN202411441461.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing oil pipeline repair coatings are insufficient in waterproofness, aging resistance and mechanical mechanical capabilities, and cannot meet the complex pipeline repair environment needs.
Compositions such as composite epoxy resin, modified epoxy resin, functional additives, etc. are used to improve the toughness of the resin and the complexity of the internal network construction by introducing flexible chain segments, reduce the particle void pore size of the filler particles, control the surface content of the filler particles, and form Continuous interfacial mask enhances the force between bonded molecules and improves adhesion, corrosion resistance, waterproof and aging resistance.
While maintaining excellent adhesion, corrosion resistance and wear resistance, it significantly improves the waterproof and aging resistance of the paint, meets the needs of complex oil pipeline repair environments, extends the service life of the pipeline and ensures safe operation.
Smart Images

Figure CN118956236B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of coatings, and in particular to a petroleum pipeline repair coating composition and a preparation method and application thereof. Background Art
[0002] Oil pipelines are important infrastructure for transporting crude oil, refined oil and natural gas. Since these pipelines are often in harsh working environments, such as high temperature, high pressure, corrosive media and complex geological conditions, they are prone to corrosion, cracks, wear and tear and other problems. In order to ensure the safe operation of the pipeline, it is necessary to regularly inspect and maintain the pipeline and repair the problem areas found. Oil pipeline repair coating is a special coating designed to repair and protect oil pipelines from corrosion, wear and other damage. This type of coating is usually used in pipeline areas that have been damaged or have potential risks to extend the service life of the pipeline and ensure its safe operation.
[0003] Traditional repair methods usually involve replacing the damaged part or using mechanical clamps for temporary fixation. However, these methods are not only costly, but may not be feasible in some cases. Therefore, the development of efficient repair coatings has become a more economical and practical option. With the advancement of technology, more and more high-performance repair coatings have been developed. These coatings are usually based on epoxy resins, polyurethanes, coal tar epoxy resins and other synthetic resin systems, and usually have good adhesion, corrosion resistance, wear resistance and weather resistance.
[0004] Although these repair coatings perform well in many cases, there are still some technical challenges. For example, the existing repair coatings have poor water resistance, aging resistance and mechanical properties, and cannot meet the complex pipeline repair environment. Therefore, in order to effectively solve the above problems, the present application provides a petroleum pipeline repair coating composition and a preparation method thereof. The petroleum pipeline repair coating composition prepared in the present application can maintain excellent adhesion, corrosion resistance, and wear resistance while having good water resistance and aging resistance, meeting the performance requirements for repair coatings in complex petroleum pipeline repair environments, and thus has excellent application prospects. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a petroleum pipeline repair coating composition, which comprises the following raw materials, in parts by mass: 70 to 90 parts of a composite epoxy resin, 20 to 30 parts of filler particles, 3 to 5 parts of an accelerator, 4 to 6 parts of a curing agent, 1 to 2 parts of a leveling agent, 1 to 2 parts of a defoaming agent, 1 to 1.5 parts of an antioxidant, and 15 to 30 parts of a functional additive.
[0006] As a preferred solution, the mass ratio of the composite epoxy resin, filler particles and functional additives is (75-85): (22-26): (18-25).
[0007] As a preferred solution, the mass ratio of the composite epoxy resin, filler particles and functional additives is (78-84): (22-24): (19-22).
[0008] As a preferred solution, the mass ratio of the accelerator, the curing agent and the leveling aid is (4-6): (5-5.5): (1.2-1.8).
[0009] As a preferred solution, the mass ratio of the accelerator, the curing agent and the leveling aid is (4.5~5): (5.2~5.5): (1.4~1.6).
[0010] As a preferred solution, the composite epoxy resin is a composition of bisphenol A epoxy resin, brominated epoxy resin and modified epoxy resin.
[0011] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, the brominated epoxy resin and the modified epoxy resin is (6-8): (1-1.5): (1-1.4).
[0012] As a preferred solution, the mass ratio of bisphenol A epoxy resin, brominated epoxy resin and modified epoxy resin is (6.5~7.5):(1.2~1.5):(1.1~1.3).
[0013] As a preferred solution, the epoxy equivalent of the bisphenol A epoxy resin is 880 g / eq.
[0014] As a preferred solution, the acid value of the bisphenol A epoxy resin is 20-30 mgKOH / g.
[0015] As a preferred solution, the brominated epoxy resin is brominated bisphenol A epoxy resin.
[0016] As a preferred solution, the epoxy equivalent of the brominated epoxy resin is 400 g / eq.
[0017] As a preferred scheme, the preparation method of the modified epoxy resin comprises the following steps: S1: under nitrogen protection, bisphenol F epoxy resin and propylene glycol triglycidyl ether are added to a reaction container, and then diphenylmethane diisocyanate and 2-ethyl-4-methylimidazole are added in sequence, and stirred to mix evenly; S2: heating to 60-75°C, keeping the temperature for reaction for 2-4 hours, and then heating to 90-110°C, and keeping the temperature for reaction for 2-4 hours to obtain a prepolymer product; S3: mixing the prepolymer product, succinic anhydride and 3-aminopropyltriethoxysilane and adding deionized water, and then transferring to a sealed reactor, controlling the reactor pressure to 1.2-1.6 MPa, heating to 140-160°C, keeping the temperature for reaction for 2.5-3.5 hours, and naturally cooling to room temperature after the reaction is completed, filtering, washing, and vacuum drying to obtain the product.
[0018] As a preferred solution, the mass ratio of the bisphenol F epoxy resin, propylene glycol triglycidyl ether, diphenylmethane diisocyanate and 2-ethyl-4-methylimidazole is (8-10): (3-4): (1-1.5): (0.01-0.05).
[0019] As a preferred solution, the epoxy equivalent of the bisphenol F epoxy resin is 300-400 g / eq.
[0020] As a preferred solution, the mass ratio of the prepolymer product, succinic anhydride and 3-aminopropyltriethoxysilane is (6-8): (1-1.2): (0.2-0.3).
[0021] In this application, the addition of the modified epoxy resin can effectively improve the adhesion, corrosion resistance, aging resistance and waterproof performance of the coating composition. The modified epoxy resin can increase the entanglement probability between molecular chains when the three-dimensional network is constructed in the system by introducing flexible segments to improve the toughness of the resin, thereby increasing the complexity of the internal network system. On this basis, the pore size of the micro-voids of the filler particles in the coating after curing can be effectively reduced, thereby avoiding the negative impact of the larger active pore size on waterproof, aging and corrosion resistance; on the other hand, the content of filler particles on the coating surface can be effectively controlled, thereby obtaining suitable wear resistance while avoiding the pore size and surface porosity of the surface pores, thereby reducing the probability of water molecules and active groups penetrating the coating, thereby obtaining good stability of various performances.
[0022] As a preferred solution, the filler particles are at least one of sericite powder, barium sulfate powder, titanium dioxide, carbon black powder and talc powder.
[0023] As a preferred solution, the filler particles are a composition of sericite powder and titanium dioxide.
[0024] As a preferred solution, the mass ratio of the sericite powder to titanium dioxide is (4-4.5): (1-1.2).
[0025] As a preferred solution, the average particle size of the sericite powder is 1.5-2.5 μm.
[0026] As a preferred solution, the average particle size of the titanium dioxide is 50-100 nm.
[0027] As a preferred solution, the accelerator is dimethylimidazole.
[0028] As a preferred solution, the curing agent is at least one of phthalic anhydride, maleic anhydride, 2-ethyl-4-methylimidazole, meta-phenylenediamine, polyamide and polyetheramine.
[0029] As a preferred solution, the curing agent is phthalic anhydride.
[0030] As a preferred solution, the leveling aid is polydimethylsiloxane or modified polysiloxane.
[0031] As a preferred solution, the leveling aid is polydimethylsiloxane.
[0032] As a preferred solution, the defoaming agent is at least one of silicone defoaming agents.
[0033] As a preferred solution, the antioxidant is at least one of antioxidant 1076, antioxidant 168, antioxidant 245, antioxidant 1098, and antioxidant 1330.
[0034] As a preferred solution, the antioxidant is antioxidant 1076.
[0035] As a preferred solution, the functional additive is a composition of epoxy block polyether and aromatic polyoxyethylene ether.
[0036] As a preferred solution, the mass ratio of the epoxy block polyether to the aromatic polyoxyethylene ether is (4.2-5.8):(1.6-2.8).
[0037] As a preferred solution, the epoxy block polyether is a composition of an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 1600Da and an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 7800Da, and the mass ratio of the two is (2~3):(1~1.2).
[0038] As a preferred solution, the aromatic polyoxyethylene ether is tristyrylphenol polyoxyethylene ether.
[0039] As a preferred solution, the HLB value of the aromatic polyoxyethylene ether is 10-13.
[0040] The above functional additives added in the present application can effectively help improve the adhesion, corrosion resistance, waterproof and aging resistance of the coating composition. The combination of epoxy block polyether and aromatic polyoxyethylene ether can form a continuous interfacial film in the coating system through their joint action. The presence of the interfacial film can effectively limit the free movement of filler particles in the coating system, and then obtain excellent uniformity under the overall filler dispersion effect, and can effectively reduce the content of titanium dioxide particles on the coating surface, thereby avoiding the decrease in waterproofness caused by the multi-hydroxy guiding effect of titanium dioxide, and in the composition system, the introduction of more copolyethers can enhance the force between bonding molecules and enhance the adhesion of the coating; on the other hand, when the interfacial film of different segment lengths contacts the epoxy resin, it can continue the molecular chain force in the epoxy resin system, thereby greatly improving the tightness of the internal three-dimensional network construction, increasing the steric hindrance in the system, and greatly increasing the penetration resistance and path of water molecules and free groups in the coating composition, thereby avoiding the active reaction of water molecules and active groups with water molecules as carriers in the composition system, and obtaining good waterproof, corrosion resistance and aging resistance.
[0041] The second aspect of the present application provides a method for preparing the above-mentioned petroleum pipeline repair coating composition, which specifically includes the following steps: S1: adding a composite epoxy resin to a high-speed mixer, preferentially adding a mixture of filler particles and functional additives, stirring at a speed of 400-600 rpm for 40-50 minutes to mix evenly, then adding the remaining raw materials in sequence, stirring at a speed of 400-600 rpm for 20-30 minutes each time the raw materials are added, and a mixture is obtained after completion; S2: adding the mixture to a twin-screw extruder for melt extrusion, the extrusion temperature is 130-140°C, the screw speed is 900-1200 rpm, the extruded material is roller cooled, and ground through an 800 mesh sieve to obtain.
[0042] The remaining raw materials are added and mixed in sequence in the preparation method of the present invention, and the order of adding does not affect the performance results of the final product.
[0043] The third aspect of the present application provides an application of a petroleum pipeline repair coating composition in ground pipeline repair, buried pipeline repair, underwater pipeline repair and high-temperature and high-pressure pipeline emergency repair.
[0044] The beneficial effects of this application are:
[0045] 1. The present application provides a petroleum pipeline repair coating composition, which can maintain excellent adhesion, corrosion resistance, wear resistance, while having good waterproof and aging resistance properties, meeting the performance requirements of the repair coating in the complex petroleum pipeline repair environment, and thus has excellent application prospects.
[0046] 2. A petroleum pipeline repair coating composition provided in the present application, the added modified resin can effectively improve the adhesion, corrosion resistance, aging resistance and waterproof performance of the coating composition; the modified epoxy resin can improve the toughness of the resin by introducing flexible chain segments, while increasing the entanglement probability between molecular chains when constructing a three-dimensional network in the system, thereby increasing the complexity of the internal network system, and on this basis can effectively reduce the pore size of the micro-voids of the filler particles in the coating after curing, thereby avoiding the negative impact of larger active pores on waterproof, aging and corrosion resistance; on the other hand, it can effectively control the content of filler particles on the coating surface, thereby obtaining suitable wear resistance while avoiding the pore size and surface porosity of surface pores, thereby reducing the probability of water molecules and active groups penetrating the coating, thereby obtaining good stability of various performances.
[0047] 3. A petroleum pipeline repair coating composition provided in the present application, wherein the functional additives used in the coating composition form a continuous interfacial film in the coating system through their joint action. The presence of the interfacial film can effectively limit the free movement of filler particles in the coating system, thereby obtaining excellent uniformity under the overall filler dispersion effect, and can effectively reduce the content of titanium dioxide particles on the coating surface, thereby avoiding the decrease in water resistance due to the multi-hydroxy guiding effect of titanium dioxide. In the composition system, the introduction of more copolyethers can enhance the force between bonding molecules and enhance the adhesion of the coating; on the other hand, when the interfacial films of different chain lengths come into contact with the epoxy resin, they can continue the molecular chain force in the epoxy resin system, thereby greatly improving the compactness of the internal three-dimensional network construction, increasing the steric hindrance in the system, and greatly increasing the penetration resistance and path of water molecules and free groups in the coating composition, thereby avoiding the active reaction of water molecules and active groups with water molecules as carriers in the composition system. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a physical picture of the petroleum pipeline repair coating composition prepared by the present invention. DETAILED DESCRIPTION
[0049] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0050] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art. Example 1
[0051] Example 1 The first aspect provides a petroleum pipeline repair coating composition, which comprises, by mass, 80.5 parts of a composite epoxy resin, 22.5 parts of filler particles, 4.8 parts of an accelerator, 5.4 parts of a curing agent, 1.5 parts of a leveling agent, 1.1 parts of a defoaming agent, 1.4 parts of an antioxidant, and 20.2 parts of a functional additive.
[0052] The composite epoxy resin is a composition of bisphenol A epoxy resin, brominated epoxy resin and modified epoxy resin, and the mass ratio of the three is 6.8:1.2:1.1.
[0053] The bisphenol A epoxy resin has an epoxy equivalent of 880 g / eq and an acid value of 25 mgKOH / g. The GESR904H product was purchased from Zhuhai Hongchang Electronic Materials Co., Ltd.
[0054] The brominated epoxy resin is brominated bisphenol A epoxy resin with an epoxy equivalent of 400 g / eq, and is purchased from Jiangyin Wanqian Chemicals Co., Ltd. under the model NPEB-400.
[0055] The preparation method of the modified epoxy resin comprises the following steps, calculated by mass: S1: under nitrogen protection, 9.6 parts of bisphenol F epoxy resin and 3.3 parts of propylene glycol triglycidyl ether are added to a reaction container, and then 1.2 parts of diphenylmethane diisocyanate and 0.021 parts of 2-ethyl-4-methylimidazole are added in sequence, and stirred to mix evenly; S2: heating to 70°C, keeping the temperature for reaction for 2.5 hours, then heating to 110°C, and keeping the temperature for reaction for 3 hours to obtain a prepolymer product; S3: mixing 7.5 parts of the prepolymer product, 1.1 parts of succinic anhydride and 0.24 parts of 3-aminopropyltriethoxysilane, adding 180 parts of deionized water, and then transferring to a sealed reactor, controlling the reactor pressure to 1.4MPa, heating to 155°C, keeping the temperature for reaction for 3 hours, and naturally cooling to room temperature after the reaction is completed, filtering and washing, and vacuum drying to obtain the product.
[0056] The epoxy equivalent of bisphenol F epoxy resin is 330 g / eq, and the equivalent product was purchased from Shandong Polychemical.
[0057] The filler particles are a composition of sericite powder and titanium dioxide, and the mass ratio of the two is 4.1:1.1.
[0058] The average particle size of sericite powder is 1.8 μm; the average particle size of titanium dioxide is 60 nm.
[0059] The accelerator is dimethylimidazole; the curing agent is phthalic anhydride; the leveling agent is polydimethylsiloxane BYK-300; the defoaming agent is silicone defoaming agent BYK-066N; and the antioxidant is antioxidant 1076.
[0060] The functional additive is a composition of epoxy block polyether and aromatic polyoxyethylene ether, and the mass ratio of the two is 4.8:1.6.
[0061] The epoxy block polyether is a composition of an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 1600Da (L42 model product purchased from BASF) and an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 7800Da (L87 model product purchased from BASF), and the mass ratio of the two is 2.5:1.1.
[0062] The aromatic polyoxyethylene ether is tristyrylphenol polyoxyethylene ether with an HLB value of 12.4, which is purchased from the corresponding product sold by Hai'an Petrochemical Company in Jiangsu Province.
[0063] The second aspect of the present embodiment provides a method for preparing the above-mentioned petroleum pipeline repair coating composition, which specifically includes the following steps: S1: adding the composite epoxy resin to a high-speed mixer, preferentially adding a mixture of filler particles and functional additives, stirring at a speed of 550 rpm for 45 minutes to mix evenly, and then adding the remaining raw materials in sequence, stirring at a speed of 500 rpm for 25 minutes each time the raw materials are added, and a mixture is obtained after completion; S2: adding the mixture to a twin-screw extruder for melt extrusion, the extrusion temperature is 130°C, the screw speed is 1000 rpm, the extruded material is roller cooled, and ground through an 800-mesh sieve to obtain. Example 2
[0064] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being: 75.6 parts of composite epoxy resin, 25.5 parts of filler particles, 4.8 parts of accelerator, 5.4 parts of curing agent, 1.5 parts of leveling agent, 1.1 parts of defoaming agent, 1.4 parts of antioxidant, and 18.5 parts of functional additives.
[0065] The composite epoxy resin is a composition of bisphenol A epoxy resin, brominated epoxy resin and modified epoxy resin, and the mass ratio of the three is 8:1:1.
[0066] The filler particles are a composition of sericite powder and titanium dioxide, and the mass ratio of the two is 4.5:1.
[0067] The functional additive is a composition of epoxy block polyether and aromatic polyoxyethylene ether, and the mass ratio of the two is 5.8:2.8.
[0068] The epoxy block polyether is a composition of an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 1600Da (L42 model product purchased from BASF) and an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 7800Da (L87 model product purchased from BASF), and the mass ratio of the two is 2:1.2. Example 3
[0069] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being: 84.2 parts of composite epoxy resin, 22.1 parts of filler particles, 4.8 parts of accelerator, 5.4 parts of curing agent, 1.5 parts of leveling agent, 1.1 parts of defoaming agent, 1.4 parts of antioxidant, and 24.4 parts of functional additives.
[0070] The composite epoxy resin is a composition of bisphenol A epoxy resin, brominated epoxy resin and modified epoxy resin, and the mass ratio of the three is 6:1.5:1.4.
[0071] The filler particles are a composition of sericite powder and titanium dioxide, and the mass ratio of the two is 4:1.2.
[0072] The functional additive is a composition of epoxy block polyether and aromatic polyoxyethylene ether, and the mass ratio of the two is 4.2:2.5.
[0073] The epoxy block polyether is a composition of an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 1600Da (L42 model product purchased from BASF) and an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 7800Da (L87 model product purchased from BASF), and the mass ratio of the two is 3:1.
[0074] Comparative Example 1
[0075] The specific implementation of this comparative example is basically the same as that of Example 1, except that: 90.5 parts of composite epoxy resin, 14.5 parts of filler particles, 4.8 parts of accelerator, 5.4 parts of curing agent, 1.5 parts of leveling agent, 1.1 parts of defoaming agent, 1.4 parts of antioxidant, and 25.5 parts of functional additives.
[0076] Comparative Example 2
[0077] The specific implementation of this comparative example is basically the same as that of Example 1, except that: 60.5 parts of composite epoxy resin, 35.5 parts of filler particles, 4.8 parts of accelerator, 5.4 parts of curing agent, 1.5 parts of leveling agent, 1.1 parts of defoaming agent, 1.4 parts of antioxidant, and 12.1 parts of functional additives.
[0078] Comparative Example 3
[0079] The specific implementation of this comparative example is basically the same as that of Example 1, except that the composite epoxy resin is a composition of bisphenol A epoxy resin, brominated epoxy resin and modified epoxy resin, and the mass ratio of the three is 9:1:0.2.
[0080] Comparative Example 4
[0081] The specific implementation of this comparative example is basically the same as that of Example 1, except that the composite epoxy resin is a composition of bisphenol A epoxy resin, brominated epoxy resin and modified epoxy resin, and the mass ratio of the three is 5:1:3.5.
[0082] Comparative Example 5
[0083] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional auxiliary agent is a composition of epoxy block polyether and aromatic polyoxyethylene ether, and the mass ratio of the two is 2.5:4.
[0084] Comparative Example 6
[0085] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the epoxy block polyether is a composition of an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 1600Da (L42 model product purchased from BASF) and an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 7800Da (L87 model product purchased from BASF), and the mass ratio of the two is 4:0.5.
[0086] Comparative Example 7
[0087] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the epoxy block polyether is a composition of an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 1600Da (L42 model product purchased from BASF) and an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 7800Da (L87 model product purchased from BASF), and the mass ratio of the two is 0.5:3.2.
[0088] Performance Evaluation
[0089] Mechanical properties: After the coating compositions prepared in the examples and comparative examples were melted, heated, cooled and solidified, 1.5 cm × 1.5 cm × 0.1 cm samples were prepared. The tensile strength and elongation at break of the samples were tested using a universal tensile testing machine. The test values were averaged over 10 tests and recorded in Table 1.
[0090] Corrosion resistance: With 5wt% NaCl as the test solution, the temperature condition is 38℃, the relative humidity is 75%, and the salt spray resistance test is carried out. The coating thickness is 0.05cm, the inclination angle is 20°, the spraying is uniform, the spray pressure is 1.5bar, and the test time is 1200h. After completion, observe whether there is blistering, oxidation, rust and cracking. If there is, it is unqualified, otherwise it is qualified. The qualified rate of 50 groups of samples in each test is recorded in Table 1.
[0091] Waterproof performance: The sessile drop method was used to test the water contact angle of the coating surface after curing of the coating composition obtained in the embodiment and the comparative example. The coating thickness was 0.05 cm, the water drop size was 2.5 μL, and the time was 30 s. The water contact angle of the coating surface was obtained. The test value was the average of 10 tests and recorded in Table 1.
[0092] Aging resistance: After the coating compositions prepared in the examples and comparative examples were melted, heated, cooled and solidified, samples of 1.5 cm × 1.5 cm × 0.1 cm were prepared. The samples were placed in a constant temperature and humidity chamber at 68°C and a relative humidity of 75% for 3 months, and then observed for blistering, oxidation, rust and cracking. If so, it was unqualified, otherwise it was qualified. 50 groups of samples were tested in each group, and the qualified rate results were recorded in Table 1.
[0093] Table 1 Performance test results
[0094] Example Tensile strength (MPa) Elongation at break (%) Corrosion resistance qualified rate (%) Waterproof-water contact angle (°) Ageing resistance qualified rate (%) Example 1 23.4 72.2 100 113.4 96 Example 2 22.9 71.1 100 110.9 96 Example 3 22.7 69.8 100 112.1 92 Comparative Example 1 22.1 70.4 88 104.1 86 Comparative Example 2 16.7 58.4 96 106.3 90 Comparative Example 3 20.8 68.4 92 98.6 84 Comparative Example 4 19.8 64.9 90 94.5 86 Comparative Example 5 18.9 65.5 82 96.3 78 Comparative Example 6 19.2 66.1 86 92.1 82 Comparative Example 7 20.5 70.7 84 94.4 84
[0095] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of mechanical properties, waterproof properties, corrosion resistance and aging resistance. This is mainly due to the combined effect of the modified functional resin, functional additives and other matching technical solutions specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. A petroleum pipeline repair coating composition, Features: In parts by mass, the raw materials are: 70-90 parts of composite epoxy resin, 20-30 parts of filler particles, 3-5 parts of accelerator, 4-6 parts of curing agent, 1-2 parts of leveling agent, 1-2 parts of defoaming agent, 1-1.5 parts of antioxidant, and 15-30 parts of functional additives; The composite epoxy resin is a composition of bisphenol A epoxy resin, brominated epoxy resin and modified epoxy resin; The mass ratio of the bisphenol A epoxy resin, the brominated epoxy resin and the modified epoxy resin is (6-8): (1-1.5): (1-1.4); The epoxy equivalent of the bisphenol A epoxy resin is 880 g / eq; the acid value of the bisphenol A epoxy resin is 20-30 mgKOH / g; The brominated epoxy resin is brominated bisphenol A epoxy resin; the epoxy equivalent of the brominated epoxy resin is 400 g / eq; The preparation method of the modified epoxy resin comprises the following steps: S1: under nitrogen protection, bisphenol F epoxy resin and glycerol triglycidyl ether are added to a reaction container, and then diphenylmethane diisocyanate and 2-ethyl-4-methylimidazole are added in sequence, and stirred to mix evenly; S2: heating to 60-75°C, keeping the temperature for reaction for 2-4 hours, and then heating to 90-110°C, and keeping the temperature for reaction for 2-4 hours to obtain a prepolymer product; S3: mixing the prepolymer product, succinic anhydride and 3-aminopropyltriethoxysilane, adding deionized water, and then transferring to a sealed reactor, controlling the reactor pressure to 1.2-1.6MPa, heating to 140-160°C, keeping the temperature for reaction for 2.5-3.5 hours, and naturally cooling to room temperature after the reaction is completed, filtering, washing, and vacuum drying to obtain the product; The mass ratio of the bisphenol F epoxy resin, glycerol triglycidyl ether, diphenylmethane diisocyanate and 2-ethyl-4-methylimidazole is (8-10): (3-4): (1-1.5): (0.01-0.05); The mass ratio of the prepolymer product, succinic anhydride and 3-aminopropyltriethoxysilane is (6-8): (1-1.2): (0.2-0.3); The filler particles are at least one of sericite powder, barium sulfate powder, titanium dioxide, carbon black powder and talc powder; The curing agent is at least one of phthalic anhydride, maleic anhydride, 2-ethyl-4-methylimidazole, m-phenylenediamine, polyamide and polyetheramine; The functional additive is a composition of epoxy block polyether and aromatic polyoxyethylene ether; the mass ratio of the epoxy block polyether to the aromatic polyoxyethylene ether is (4.2-5.8): (1.6-2.8); The epoxy block polyether is a composition of an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 1600Da and an ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 7800Da, and the mass ratio of the two is (2-3): (1-1.2); The mass ratio of the accelerator, curing agent and leveling agent is (4-6): (5-5.5): (1.2-1.8); The accelerator is dimethylimidazole; The antioxidant is at least one of antioxidant 1076, antioxidant 168, antioxidant 245, antioxidant 1098, and antioxidant 1330.
2. The petroleum pipeline repair coating composition according to claim 1, Features: The mass ratio of the composite epoxy resin, filler particles and functional additives is (75-85): (22-26): (18-25).
3. The petroleum pipeline repair coating composition according to claim 2, Features: The filler particles are a composition of sericite powder and titanium dioxide; the mass ratio of the sericite powder to titanium dioxide is (4-4.5): (1-1.2).
4. The petroleum pipeline repair coating composition according to claim 3, Features: The average particle size of the sericite powder is 1.5-2.5 μm; the average particle size of the titanium dioxide is 50-100 nm.
5. The petroleum pipeline repair coating composition according to claim 4, Features: The leveling aid is polydimethylsiloxane or modified polysiloxane.
6. A method for preparing the petroleum pipeline repair coating composition according to any one of claims 1 to 5, Features: The specific steps include: S1: Add the composite epoxy resin into a high-speed mixer, preferably add the mixture of filler particles and functional additives, stir at 400-600 rpm for 40-50 min to mix evenly, then add the remaining raw materials in sequence, stir at 400-600 rpm for 20-30 min each time the raw materials are added, and a mixture is obtained after completion; S2: Add the mixture into a twin-screw extruder for melt extrusion, the extrusion temperature is 130-140°C, the screw speed is 900-1200 rpm, the extruded material is roller cooled, and ground through an 800-mesh sieve to obtain the obtained material.
7. Use of the petroleum pipeline repair coating composition according to any one of claims 1 to 5 in surface pipeline repair, buried pipeline repair, underwater pipeline repair and high-temperature and high-pressure pipeline emergency repair.
